THE IMPACT OF GENDER EQUALITY EDUCATION ON THE ETHICAL STRUCTURE OF CHINESE FAMILY-THEMED FILMS IN THE NEW CENTURY - Dan Cheng (Fonseca, Journal of Communication, 2024)
Gender equality education is an important aspect of promoting a fair society. Chinese family-themed movies have a distinctive ethical framework that frequently reflects the standards and values of Chinese culture. In light of this, studying and investigating these films might reveal how gender equality is viewed and promoted in Chinese society. The impact of gender equality education on the moral framework of Chinese family-themed movies in the twenty-first century is investigated in this study. Films can be used to question conventional ideas about gender roles and gender stereotypes. They are a strong medium for promoting principles and messages of gender equality. The moral implications of movies can reveal whether or not the Chinese people support the idea of gender equality. The study uses a quantitative methodology, examining several Chinese family-themed movies and gathering information from media sources. Over three days, information from 200 respondents was gathered from media persons using a convenience sampling technique. Smart PLS 3 statistical software was used to evaluate the data (SEM). The results point to a strong influence of gender equality education on how gender roles and family relationships are portrayed in Chinese cinema, with a discernible movement towards more diverse and egalitarian portrayals. Nonetheless, the ethical framework of Chinese family-themed movies is also still being shaped by the influence of conventional cultural values and business considerations. To encourage more inclusive and empowering representations of gender and family in Chinese cinema, the study’s conclusion highlights the possibility of gender equality education.